Initial Experience with the EndoFusion 3D System for Noninvasive Intraoperative Localization of Pulmonary Nodules - Gan, Wei; Yu, Yi; Peng, Wu-Ke; Huang, Qi-Lin; Peng, Xiao-Yue; Ye, Chun-Lin (Journal of Thoracic Disease; Online First, 2026)
Background: Intraoperative localization of small peripheral pulmonary nodules remains difficult during video-assisted thoracoscopic surgery (VATS), especially for subcentimeter and ground-glass–predominant lesions. Conventional computed tomography (CT) guided localization is effective but invasive and carries radiation exposure and puncture-related risks. This study assessed the feasibility and safety of EndoFusion, a system that projects preoperative 3D information onto real-time thoracoscopic views to assist localization.Methods: A single-center retrospective study was conducted on patients undergoing VATS sublobar resection with EndoFusion-assisted localization. Preoperative 3D models were generated from thin-slice CT and registered to the pleural surface intraoperatively. Technical success, localization accuracy, perioperative outcomes, and complications were assessed.Results: Fifteen patients with a total of 19 peripheral pulmonary nodules were included. The median nodule size was 8.0 mm and the median pleural depth was 3.0 mm, with most lesions characterized as pure ground-glass nodules (pGGNs) or consolidation-to-tumor ratio (CTR) ≤0.25. All patients successfully underwent VATS resection without conversion, including wedge resection (60.0%), combined wedge and segmentectomy (26.7%), or segmentectomy (13.3%). The median operative time was 75 minutes, and EndoFusion registration was completed in a median of 128 seconds. Intraoperative blood loss was minimal (median 50 mL), and no intraoperative complications occurred. Two patients (13.3%) developed minor postoperative complications, and the median hospital stay was 4 days.Conclusions: EndoFusion provides a feasible, safe, and fully noninvasive intraoperative localization method for VATS. By projecting patient-specific 3D anatomy directly onto the operative field, it enhances precision, reduces cognitive burden, and may serve as an effective alternative to conventional preoperative localization.